Community-Associated Methicillin-Resistant Staphylococcus aureus in a Pediatric Emergency Department in Newfoundland and Labrador. Issue 1 (2014) - Peebles, Erin; Morris, Robert; Chafe, Roger
Abstract : BACKGROUND: First-generation cephalosporins and antistaphylococcal penicillins are typically the first choice for treating skin and soft tissue infections (SSTI), but are not effective for infections caused by methicillin-resistant Staphylococcus aureus (MRSA). It is currently unclear what percentage of SSTIs is caused by community-associated MRSA in different regions in Canada. OBJECTIVES:To determine the incidence of MRSA in children presenting to a pediatric emergency department with SSTI, and to determine which antibiotics were used to treat these infections. METHODS: All visits to a pediatric emergency department were reviewed from April 15, 2010 to April 14, 2011. Diagnoses of cellulitis, abscess, impetigo, folliculitis and skin infection (not otherwise specified) were reviewed in detail to determine whether a culture was taken and which antibiotic was prescribed. RESULTS: There were 367 cases of SSTI diagnosed over the study period. Forty-five (12.3%) patients had lesions that were swabbed for culture and sensitivity. S aureus was the most common organism found, with 14 (66%) methicillin-sensitive cases and seven (33%) methicillin-resistant cases. Of the seven cases of MRSA identified, only one patient had clear risk factors for hospital-acquired MRSA. First-generation cephalosporins were initially prescribed for 280 (76%) patients. CONCLUSIONS: The overall incidence of MRSA in the population presenting to a pediatric emergency department in Newfoundland and Labrador appeared to be low, although only a small percentage of infections were cultured. At this time, there appears to be no need to change empirical antibiotic coverage, which remains a first-generation cephalosporin.